Demonetization to E-Monetisation in India : The Way Forward - Narayanaswamy, T.; Muthulakshmi, A. P. (Indian Journal of Finance, 2017)
The study threw light on various events that happened after demonetization of 500 and 1000 rupee notes in India after November 8, 2016. The information required for the study was collected from media reports. In the first section of the paper, the history of demonetization in India and other emerging countries was discussed. In the next section, implications of current demonetization (2016) were discussed. The media reports indicated that 80% of the money transactions are based on physical cash which, in turn, opens the door for the problems like corruption, black money, terrorism funding, etc. Cashless economy (which means use of minimum cash and the rest of the transactions through different electronic modes of transactions) will greatly solve the above problems. Adding to this, the ideology of Bokil Anil of Arthakranthi Foundation on cashless economy and their benefits, if implemented, were also discussed.